2017
DOI: 10.1080/10256016.2017.1302446
|View full text |Cite
|
Sign up to set email alerts
|

Tightly bound soil water introduces isotopic memory effects on mobile and extractable soil water pools

Abstract: Cryogenic vacuum extraction is the well-established method of extracting water from soil for isotopic analyses of waters moving through the soil-plant-atmosphere continuum. We investigate if soils can alter the isotopic composition of water through isotope memory effects, and determined which mechanisms are responsible for it. Soils with differing physicochemical properties were re-wetted with reference water and subsequently extracted by cryogenic water distillation. Results suggest some reference waters bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 32 publications
8
53
3
Order By: Relevance
“…The isotopic composition of the water remaining in soil for exchange in the L or H treatments (δ 2 H = −141.9 mUr and δ 18 O = −13.10 mUr) is strongly depleted compared with the extracted water (δ 2 H = −52.2 mUr and δ 18 O = −7.68 mUr), an effect that has also been observed by Newberry et al and Oshun et al – the latter assumed clay interaction to be the driving force for this effect.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The isotopic composition of the water remaining in soil for exchange in the L or H treatments (δ 2 H = −141.9 mUr and δ 18 O = −13.10 mUr) is strongly depleted compared with the extracted water (δ 2 H = −52.2 mUr and δ 18 O = −7.68 mUr), an effect that has also been observed by Newberry et al and Oshun et al – the latter assumed clay interaction to be the driving force for this effect.…”
Section: Discussionsupporting
confidence: 89%
“…A number of laboratory experiments where oven‐dried soil was spiked with water of known isotopic composition have shown that the added water could not be reliably recovered from the soil . It remained unclear, however, whether this was due to inefficient performance of the cryodistillation setup – which widely differs among laboratories – or to interaction or exchange of the added water with the soil matrix and/or residual soil water, a process that has been referred to as memory effect . The basis for the memory effect is the assumption that soil water can be separated into at least two pools, the mobile soil water (which is assumed to be extractable by cryogenic vacuum extraction) and the soil‐bound water (which is not extracted by cryogenic vacuum extraction, referred to here as residual soil water) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently reported potential effects of CO 2 on the isotope analysis of vapor with wavelength-scanned cavity ring-down spectroscopy (Gralher et al, 2016) have been shown to not apply to the OA-ICSO that we used, as shown by Sprenger et al (2017a). Potentially fractionating effects of interactions between soil water and surfaces of clay minerals (Oerter et al, 2014;Gaj et al, 2017a, b;Newberry et al, 2017) are of minor relevance for our study, since clay contents were low in the sampled soils (Table 1). We can further ensure that the sampled soil volumes always contained much more than 3 g of water as suggested by Hendry et al (2015).…”
Section: Sampling Design and Analysismentioning
confidence: 92%
“…Many of these studies report extracted soil water δ 18 O and δ 2 H values that are significantly 2 H‐ or 18 O‐depleted from reference waters. It is suggested that this isotopic depletion can influence δ 2 H and δ 18 O and values independently (Orlowski et al, ) and that these effects can be exacerbated by low soil water content (Walker et al, ), soil physiochemical properties such as soil texture and clay content (Newberry et al, ; Oerter et al, ), as well as carbonate content (Meißner et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The 2 H‐ and 18 O‐depletion of extracted soil waters from added reference waters has been shown to be particularly relevant during the extraction of a spiked soil in laboratory experiments where the soil was previously dried under high temperatures in a drying oven (Newberry et al, ). It has been proposed that these effects result from the presence of two different water pools in soils: tightly bound cryogenically unextractable soil water (e.g., water adhesively bound to soil particles) and “mobile” cryogenically extractable soil water (free flowing water and capillary water; Araguás‐Araguás et al, ; Hsieh, Savin, Kelly, & Chadwick, ; Koeniger et al, ; Savin & Epstein, ).…”
Section: Introductionmentioning
confidence: 99%